Program Telehealth Pada Orang Tua Anak Dengan Autism Spectrum Disorder (ASD) di Negara Berpenghasilan Rendah dan Menengah: Sebuah Tinjauan Pelingkupan - Tittandi, Nindya Alifia; Handoyo, Restu Tri (Faculty of Psychology, Universitas Surabaya, 2026)
Parents have been identified as the main caregivers of children with Autism Spectrum Disorder (ASD), as they are actively involved in intervention strategies. There has been paucity of evidence regarding telehealth program aiming to support parents with children with Autism Spectrum Disorder (ASD) in low-and middle-income (LAMI) countries. This scoping review aims to explore and map such evidence to develop and improve such program. A systematic effort was made by reviewing research articles that involved: (1) parents of children with Autism Spectrum Disorder (ASD; age 0-18 years) as participants; (2) provided stand-alone telehealth programs (without in-person combinations); and (3) conducted in low- and middle-income (LAMI) countries; including original study and excluding review and opinion paper, with no limitation regarding research methodology nor publication date. Four academic databases were searched, namely: (1) Medline (EBSCOhost); (2) ProQuest; (3) Scopus; and (4) Science Direct; complemented with Google Scholar Search. Keywords were derived from three main keywords: (1) ‘telehealth’; (2) ‘parent’; and (3) ‘autism spectrum disorder’. Study selection was collated together in software Zotero for duplication screening. Afterwards, all articles were imported into Rayyan for title and abstract screening, followed by full-text analysis. The information charting process utilized the charting form developed specifically for this scoping review by independent testing on three articles by two reviewers. Any discrepancies between the two reviewers were resolved through discussion and decision from a third reviewer. The study selection process is reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. Seven articles were obtained after the search and screening process. The characteristics of telehealth programs aimed for parents of children with Autism Spectrum Disorder (ASD) are based on the review, such as: (1) telehealth is aimed at increasing parents' skills in caring for children with Autism Spectrum Disorder (ASD); and/or (2) reducing the stress and anxiety levels of parents while caring for children with Autism Spectrum Disorder (ASD). The programs were delivered by video conferencing, audio calls, and text messages–using the devices of each participant. Programs could involve various parties to collaborate, such as professionals, therapists, and/or certain agencies. Systematic program in the form of material components and duration of implementation is also important to note, so that the telehealth programs could meet the needs of parents and children with Autism Spectrum Disorder (ASD), especially in the low- and middle-income (LAMI) countries.